Dampak Pandemi Covid 19 Terhadap Penetapan Tarif Bis AKAP Berdasarkan BOK dan BEP (studi kasus : PO. X rute trayek Jakarta – Malang tahun 2020) - Marpaung, Edward; Irenita, Novembriani; Dewa, Yuhas Amara (Institut Transportasi dan Logistik Trisakti, 2022)
PO. X is a bus company that provides inter-city and inter-provincial bus transportation services that have been operating since 2011 with the Jakarta – Malang route. The existence of a load factor limitation by the government makes bus operators conduct a re-examination in setting tariffs. The purpose of this study is to find out how much a reasonable rate is set by the company based on the Break Event Point (BEP). This research uses a descriptive quantitative method. The results of data analysis show that a reasonable rate is set based on the Vehicle Operating Cost (BOK) of Rp. 284,166 at the LF level of 70% and experienced an increase in tariffs of 29% when the LF became 50%, and decreased by 30% when the LF was at the 100% level. The minimum tariff that has been calculated based on the BEP is Rp. 199,547 at a load factor of 70%. Therefore, the rate set based on the company's BOK is in accordance with the BEP.